Efecto de la altura de vuelo en aplicación aérea, en áreas influenciadas por obstáculos para el control de sigatoka negra en el cultivo de banano (Musa spp.) cantón Vinces. - Cruz Torrico, José Fernando (2016)
The aim of this research was to determine the effect of the flight altitude aerial application, influenced by obstacles to the control of black sigatoka in banana growing (Musa spp) Vinces Canton areas, whose geographical location is a altitude of 28 meters. Its geographical coordinates are 70 ° 21 'west longitude, 1 ° 06' South latitude. design complete block at random (DBCA) with four treatments and four replications was used, the results indicate that there was a high statistical significance for the treatments and repetitions in the evaluated variables, in the evolutionary state of the 3rd and 4th leaf infection higher in both sheets presented with T3 treatment at a height of 25m, with values of 351.25 to 387.50 for 4th-3rd- and instead the lowest values of levels of infection occur in the control treatment values from 192.25 at 3rd and 213 in the 4th, in the stover 0 weeks and full of leaves (TH) in all variables (HVLE, HVLQ, HVLQ 5% TH) the best result shows the applications made 5 m in all cases is statistically superior to the values of the other treatments, with values HVLE 10.93, 15.08 HVLQ, 15.35 HVLQ 5% and TH 16, Stover 10 weeks and total leaves (TH) in all variables (HVLE, HVLQ, HVLQ 5% TH) the best result shows the applications made 5 m in all cases is statistically superior to the values of other treatments, with values HVLE 4.08, HVLQ 10.00, 10.58 HVLQ 5% and TH 11.